International accounting - Choi, Frederick D. S
Includes bibliographical references and index; Introduction -- Development and classification -- Comparative accounting : Europe -- Comparative accounting : the Americas and Asia -- Reporting and disclosure -- Foreign currency translation -- Financial reporting and changing prices -- Global accounting and auditing standards -- International financial statement analysis -- Managerial planning and control -- Financial risk management -- International taxation and transfer pricing